The analysis and choice of the system for attaining vacuum in a 300 MeV electron storage ring - Grevtsev, V.G.; Zelinsky, A.Yu.; Karnaukhov, I.I.; Mocheshnikov, N.I. (Вопросы атомной науки и техники, 2003)
Conditions are considered for attaining a pressure of ~10⁻⁹ Torr in a vacuum chamber of the redesigned storage ring N100M with the use of both concentrated and distributed pumps. Estimates are made for admissible outgassing due to thermal desorption and synchrotron radiation-induced desorption; a variant of arranging the pumps along the perimeter of the N100M storage ring is proposed.